PENDEKATAN PERSUASIF MENGATASI VACCINE HESITANCY MELALUI EDUKASI MANAJEMEN RISIKO KIPI DI DESA LEMBENGAN, LEDOKOMBO, JEMBER - ayu nouva zurraida; nining khulaifah; Siti Aprilia Rahmawati; Septiana Vergi; Ervin Chrisna; Henry Wulandari; Dwi Dhesty; Iswati Sulaiha; Dewi Ratih Sekarningrum (Jurnal SADEWA, 2026)
Vaccine hesitancy is the delay in acceptance or refusal of vaccines despite the availability of vaccines and evidence supporting their effectiveness. This is a complex problem influenced by various factors, not merely the inability to access vaccines. A persuasive approach is a relaxed and communicative method of communication that prioritizes psychological aspects, awareness, and building trust to achieve mutual agreement voluntarily. The purpose of this activity is to increase immunization coverage by reducing public vaccine hesitancy through education on AEFI (Adverse Events Following Immunization) risk management, so that parents have an understanding and practical skills to independently and confidently handle post-vaccination reactions. The methodology includes situation analysis and planning, implementation through risk management education of AEFI, and evaluation. Evaluation is conducted by assessing participants’ understanding the procedures for handling AEFI at home, measuring the level of parents' anxiety about the vaccine through a short questionnaire to see if they feel more confident (self-efficacy) in facing AEFI risks.